2021
DOI: 10.1186/s13099-021-00435-3
|View full text |Cite
|
Sign up to set email alerts
|

A re-testing range is recommended for 13C- and 14C-urea breath tests for Helicobacter pylori infection in China

Abstract: Background The urea breath test (UBT) is widely used for diagnosing Helicobacter pylori infection. In the Shenzhen Kuichong People’s Hospital, some UBT findings were contradictory to the histology outcomes, therefore this study aimed to assess and compare the diagnostic performance of both 13C- and 14C-UBT assays. Methods We recruited 484 H. pylori-treatment naïve patients, among which 217 and 267 were tested by the 13C-UBT or 14C-UBT, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…[22] A recent study revealed a sensitivity of 96.9% for 14 C-UBT but a specificity of only 54.7% or 76.9% after adjusting the cutoff values. [23] In the present study, the cutoff values were those recommended by the manufacturer, and the observed sensitivity and specificity were close to that of the 2 meta-analyses. [21,22] In terms of safety, during the trial, 1 participant experienced 1 AE (incidence rate of 0.4%).…”
Section: Discussionsupporting
confidence: 84%
“…[22] A recent study revealed a sensitivity of 96.9% for 14 C-UBT but a specificity of only 54.7% or 76.9% after adjusting the cutoff values. [23] In the present study, the cutoff values were those recommended by the manufacturer, and the observed sensitivity and specificity were close to that of the 2 meta-analyses. [21,22] In terms of safety, during the trial, 1 participant experienced 1 AE (incidence rate of 0.4%).…”
Section: Discussionsupporting
confidence: 84%
“…The trade-off between sensitivity and specificity must be put in mind in clinical setting, when selecting the assessment technique[ 31 ]. For instance, liquid scintillation counting is the recommended method when high sensitivity is essential to bypass missing true results, while solid scintillation counting could be a better selection, when high specificity is crucial to minimize false positives.…”
Section: C-ubt Performance: Urea Dose Timing Of Assessment and Choice...mentioning
confidence: 99%